The Extent of the Commitment of Islamic Banks Operating in the City of Hebron to Disclose Social Responsibility in the Published Financial Statements - Abueid, Raed; Tbakhi, Amani (International Journal of Islamic Business & Management, 2020)
The research aimed to identify the extent of the commitment of Islamic banks in the city of Hebron to disclose social responsibility in the published financial statements, where a questionnaire was designed to answer the study questions. The questionnaires were distributed to all workers in Islamic banks operating in the city of Hebron, and the study concluded that the extent of The commitment of Islamic banks to disclose social responsibility in the financial data published in the city of Hebron was a high degree within its social responsibility, and the results also showed that there are obstacles when Islamic banks in the city of Hebron disclosed their activities in the areas of social responsibility, and the researchers have recommended the necessity of providing training courses for workers In Islamic banks, to introduce them to the strategy of disclosing social responsibility and its importance, as one of the strategies that contribute to achieving excellence in performance in general, and the need for the Monetary Authority to issue special legislation, related to the adoption of Islamic banks to disclose their commitment to social responsibilities due to its implications for the performance of society.